War and trauma in chimamanda ngozi adichie's half of a yellow sun and chris abani's song for night - Che Jamal, Inna Malissa (2015)
Half of a Yellow Sun written by Chimamanda Ngozi Adichie and Song for Night by Chris Abani are two Nigerian civil war novels filled with tragedy, human disputes and survival. From the horrors of war and to the violence inflicted by a member of the family, trauma affects a person not only physically but also psychologically. This study attempts to elucidate the trauma concept of ‘acting-out’ and ‘working-through’ by Dominick LaCapra of the main characters of the selected Nigerian texts. Recounting the horrors of the civil war between two regions of Africa, the chosen literary texts portray the sufferings and changes that the characters undergo through pre, during and post war. the war had brought suffering and had disturbed them terribly which caused recurring psychological distress. This research explores the extent of trauma that the characters of both novels go through in a war torn country. It is also to see whether they were able to heal from their pain or delve deeper into their trauma and have no sense in coming back to face the real world. People are ignorant to the horrors that a distressing event may come to affect a person unless they are experiencing it. The concepts of ‘acting-out’ and ‘working-through’ by the theorist Dominick LaCapra with the support of works on trauma by Cathy Caruth were utilized in order to understand the characters’ trauma. The findings from the research show that the selected characters studied went through various ways of ‘acting-out’ and ‘working-through’ their trauma. Therefore, trauma affects people differently and the way that they cope with it also differs. It can be concluded that, this study enlightens readers on how both Adichie and Abani depict trauma as a force that affects the human lives based on their characters.